(untitled) (Web of Teachers: Inderscience Research, 2025)
Building a vocabulary base is a fundamental component of learning any foreign language. In recent times technology has introduced several innovative ways to enhance this process. This study observes the effectiveness of vocabulary-building technologies, such as mobile applications, spaced repetition systems, artificial intelligence (AI), and virtual reality (VR), in foreign language acquisition. With a mixed-methods approach, we conducted a survey of 150 language learners and interviewed 10 foreign language instructors. Results show that technology-based learning noticeably improves vocabulary retention, engagement, and accessibility. However, there are still challenges such as over-reliance on technology and the need for contextual learning. These outcomes suggest that while technology can offer a number of benefits, its integration with traditional learning methods should be balanced.